The notion of interpretation and commentary in Islam: projecting a true and guided meaning of texts - Jusoh, Che' Razi (Zes Rokman Resources, 2016)
One of today’s predicaments in Islamic society is when interpretation is no longer guided as though it is merely one’s right to interpret anything according to one’s whims and passions and that is in contradiction with the spirit of Islam. The notion of interpretation or commentary in Islamic scholarship has played a great and significant role in shaping the Muslims’ way of thinking for so long. Interpreting and commenting on texts started with the interpretation of primary references in Islam, i.e. al-Qur’an and al-Hadith, followed by other reliable and authentic sources such as texts (mutun), commentaries and glosses (hawashi and syuruh) of renowned and notable scholars to name but a few like Imam Abi al Hassan al-Ash’ari (d. c. 935/936,) in Creed of Islam, Imam Idris al Shafi’i (d. 150/204) in Jurisprudence and Imam al-Ghazzali (d. 1058-1111) in ethics, etc. The processes of interpreting and commenting are paramount since unscrupulous understanding of certain works could lead to deviant teachings that by all means disturb the dissemination of the true meaning of Islam. Thus, in giving interpretation and commentary on certain texts, one should follow the methodology which has been applied by the majority of scholars from the early period of Islam until the present time. Producing one’s work in free and unbound rules of interpretation could jeopardize the meaning and simultaneously yield to misinterpretation in many sorts. This paper shall embark on the importance of correct methodology in explaining religious texts vice versa to expose the tradition of interpretation and commentary applied in Islam which has been successfully guided a true meaning of the text.